Financial distress analysis using the Altman Z-Score method at CV Arthatex for the period 2022-2024 - Rahmadani, Devita Putri; Laksmi, Ayu Chairina (Proceeding International Conference on Accounting and Finance, 2026)
Financial distress is a condition of financial difficulty experienced by a company before it reaches the stage of bankruptcy. One effective method for the early detection of this condition is the Altman Z-Score model. Early detection of financial distress is crucial for management to implement strategic measures to ensure business sustainability. This research aims to analyze the level of financial distress and bankruptcy potential at CV Arthatex during the 2022–2024 period using the Modified Altman Z-Score method. This study employs a quantitative descriptive approach, utilizing secondary data from CV Arthatex’s financial statements, consisting of the balance sheets and income statements for the 2022–2024 period. The results indicate that in 2022 CV Arthatex was in a healthy financial condition (safe zone) with a Z-Score of 4.34, posing no risk of bankruptcy. However, in 2023 and 2024, the Z-Score drastically decreased to -50.22 and -72.80, respectively, placing the company in the distress zone and indicating a high potential for bankruptcy. This study proves that the Altman Z-Score method can be utilized as an effective early warning system for assessing a company’s bankruptcy risk. The findings are expected to serve as a reference for the management of CV Arthatex in making strategic decisions to improve its financial condition and prevent bankruptcy.